Efeitos de combinações de mutantes do endosperma do milho (Zea mays L.) sobre os teores de amido e de amilose de amido - M Barbosa, Hélio; V Glover, David (Revista Ceres, 2025)
The genetic materials used in this study were derivatives of the maize inbred Oh 43, and consisted of: (a) single mutant versions, each homozygous for only one of the genes ae, bt, btp, du, fiz, fly, h, 0p, shy, su, sup, and wz; (b) 10 double mutant versions involving 07 with each one of the other genes (except sh); and, (c) 11 double mutant versions involving fl, with each one of the other genes. The normal Oh 43 inbred was also included for comparison. The objective was to determine the effects, if any, of the op and fI, genes on starch percent and amylose percent of starch when each of these genes is combined with other endosperm mutants.